Disulfiram with or without metformin inhibits oesophageal squamous cell carcinoma in vivo. (28th March 2018) - Jivan, Rupal; Peres, Jade; Damelin, Leonard Howard; Wadee, Reubina; Veale, Robin Bruce; Prince, Sharon; Mavri-Damelin, Demetra
Abstract: Oesophageal squamous cell carcinoma (OSCC) is highly prevalent in developing countries but there has been little recent progress into efficacious yet affordable treatment strategies. Drug repurposing is one attractive approach for cancer therapy. Disulfiram (DSF), used to treat alcoholism, inhibits cancer growth and we previously found that DSF perturbs protein degradation/turnover pathways in vitro . This was enhanced by combining DSF with the anti-diabetic drug metformin (Met). Here, we investigated DSF with/without Met, against OSCC in vivo . Nude mice injected subcutaneously with the human OSCC cell line WHCO1, were treated with 30 mg/kg or 50 mg/kg DSF three times per week and with/without Met, for 21 days. DSF and DSF/Met-treated animals had significantly smaller tumours compared to untreated, vehicle and positive control cisplatin-treated groups. This effect for DSF was independent of copper, with no significant accumulation of copper in tumours, together with maintained proteasome activity. However, increases in total ubiquitinated proteins, LC3B-II, LAMP1 and p62 in DSF and DSF/Met groups, indicate that autophagy is inhibited. These findings show that DSF and DSF/Met significantly impede OSCC tumour growth in vivo and offer prospective alternative chemotherapy approaches for OSCC. Highlights: OSCC is highly prevalent in developing, resource-limited countries. Disulfiram is an attractive cancer chemotherapy candidate for drug repurposing. DSF with or without metformin reduces OSCC tumour growth in vivo.